Neural correlates of distinct levels of predatory threat in dorsal periaqueductal grey neurons. (7th March 2022) - Bindi, Ricardo P.; Maia, Ricardo G. O.; Pibiri, Francesca; Baldo, Marcus Vinicius C.; Poulter, Steven L.; Lever, Colin; Canteras, Newton S.
Abstract: The dorsal periaqueductal grey (PAG) is an important site for integrating predatory threats. However, it remains unclear whether predator‐related activation in PAG primarily reflects threat itself and thus can distinguish between various degrees of threat, or rather reflects threat‐oriented behaviours, with the PAG potentially orchestrating different types of defensive repertoire. To address this issue, we performed extracellular recording of dorsal PAG neurons in freely behaving rats and examined neuronal and behavioural responses to stimulus conditions with distinct levels of predatory threat. Animals were sequentially exposed to a nonthreatening stimulus familiar environment (exposure to habituated environment) and to a novel nonthreatening stimulus (i.e., a toy animal—plush) and to conditions with high (exposure to a live cat), intermediate (exposure to the environment just visited by the cat, with remnant predator scent), and low (exposure on the following day to the predatory context) levels of predatory threat. To test for contributions of both threat stimuli and behaviour to changes in firing rate, we applied a Poisson generalized linear model regression, using the different predator stimulus conditions and defensive repertoires as predictor variables. Analysis revealed that the different predator stimulus conditions were more predictive of changes in firing rate (primarily threat‐induced increases) than the different defensive repertoires. Thus, the dorsal PAG may code for different levels of predatory threat, more than it directly orchestrates distinct threat‐oriented behaviours. The present results open interesting perspectives to investigate the role of the dorsal PAG in mediating primal emotional and cognitive responses to fear‐inducing stimuli. Abstract :